Advanced materials for waste water treatment - Ul-Islam, Shahid (Advanced material series, 2017)
Over the past few decades, rapid industrialization, fast urban encroachment, and improved agricultural operations have introduced substantial amounts of potentially toxic organic substances into the atmosphere and into the aquatic and terrestrial environments. Advanced Materials for Wastewater Treatment brings together innovative methodologies and research strategies to remove toxic effluents from wastewaters.With contributions from leading scientists from all around the world, the book provides a comprehensive coverage of the current literature, up-to-date overviews of all aspects of toxic chemical remediation including the role of nanomaterials.